The effect of using polypropylene fibers on the durability and fire resistance of concrete (Fracture and Structural Integrity, 2021)
In order to study the effect of polypropylene fibers on the durability of cementitious composites, several experimental tests have been carried out in the laboratory. The composite was tested with different volume fractions of polypropylene fibers (0.05%, 0.10%, 0.30% and 0.50%). All the results relating to the indicators (porosity accessible to water εb, to the oxygen permeability Kapp.gas and diffusivity Dns) indicate that the addition of polypropylene fibers in a cement matrix represents only a small effect on durability. This panel of general sustainability indicators can be supplemented by indicators more specific to each degradation process identified or envisaged depending on the environmental conditions of the structure. However, the addition of the volume fraction of polypropylene fibers (0.50%) in a cementitious composite, increases fire resistance. Such behavior gives fiber composites interesting properties which favor their use in structures exposed to fire risks.
Keywords: Polypropylene fibers; concrete; porosity; permeability; diffusivity; durability; fire resistance